MANAJEMEN PENGELOLAAN TAMBAK IKAN BANDENG DESA LABUHAN KURIS KECAMATAN LAPE KABUPATEN SUMBAWA - muhammad kadafi prawiro; Arif Budi Witarto (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
Many pond farmers cultivate milkfish by using traditional and semi-intensive system, whereas the difference of system used will generate the difference of farmer's revenue. The aim of this research is to know the comparison of milkfish pond's productivity level by traditional and semi-intensive system in Labuhan Kuris, Lape subdistrict. Sampling technique applies Purpose Sampling method and data analysis method be used is Mann-Whimey U-test. The result of average test of milkfish pond's productivity data within traditional and semi-intensive system gets p value < 0.05 means that there is significant difference between productivity data, where intensive system productivity is higher than traditional system. The result of average test of milkfish pond's yields data within traditional and semi-intensive system gets p value < 0.05 means that there is significant difference between yields data, where the yields of intensive system is greater than traditional system.